2005
DOI: 10.1002/j.1556-6978.2005.tb00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Elements of Supervision in Sexual Violence Counselors' Narratives: A Qualitative Analysis

Abstract: The literature on vicarious traumatization has suggested that traumasensitive supervision may help to minimize the effects of vicarious exposure to trauma; however, nothing from the perspective of trauma counselors was noted. The present qualitative study involved 1 male and 8 female sexual violence counselors who had worked with sexual violence survivors from 1 to 9 years. The use of semistructured interviews and basic interpretive analysis revealed 4 themes: counselor feelings, vicarious traumatization, help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 15 publications
(17 reference statements)
1
43
0
Order By: Relevance
“…The importance of the organisation's understanding of VT and the support they offer was highlighted (Statements 3d [SD 01.57, mean 0 8.93] and 25a [SD 01.22, mean 08.00]), and is consistent with Sommer and Cox's (2005) study where therapists expressed the need for agency support for VT that included specific and ongoing training and prevention, as well as recognition and valuing of supervision as a priority. This is similarly echoed in Collins's (2003) research, which concluded that there was a 'need for educators, managers and caregivers to be aware of the possible consequences of dealing with trauma and to take positive steps to minimize the negative effects' (p. 26).…”
Section: Organisationsupporting
confidence: 57%
See 1 more Smart Citation
“…The importance of the organisation's understanding of VT and the support they offer was highlighted (Statements 3d [SD 01.57, mean 0 8.93] and 25a [SD 01.22, mean 08.00]), and is consistent with Sommer and Cox's (2005) study where therapists expressed the need for agency support for VT that included specific and ongoing training and prevention, as well as recognition and valuing of supervision as a priority. This is similarly echoed in Collins's (2003) research, which concluded that there was a 'need for educators, managers and caregivers to be aware of the possible consequences of dealing with trauma and to take positive steps to minimize the negative effects' (p. 26).…”
Section: Organisationsupporting
confidence: 57%
“…The importance of this aspect of trauma supervision is mirrored in Sommer and Cox's (2005) study, which highlights that supervisees value supervisors who acknowledge, validate and recognise that VT exists.…”
Section: Vicarious Traumatisation (Vt)mentioning
confidence: 75%
“…The findings of studies conducted to date indicate that supervision facilitates coping among populations such as women therapists working with victims of sexual trauma, therapists working with trauma victims, and telephone counselors (Dunkley & Whelan, 2006;Hollingsworth, 1993;Pearlman & MacIan, 1995;Sommer & Cox, 2005). At the same time, other studies conducted among therapists working with trauma victims and social workers in hospitals found no significant correlation between supervision and posttraumatic symptoms among therapists (Dekel, Ginzburg, & Hantman, 2004;Kassam-Adams, 1995).…”
Section: Supervision Secondary Traumatization and Burnoutmentioning
confidence: 86%
“…counselors whose work setting does not offer quality clinical supervision may want to consider finding a skilled supervisor outside their workplace-someone whom they respect and can offer an alternative lens through which to view clients and the work. it is also important that the supervisor is knowledgeable about vicarious traumatization, supports disclosures regarding the counselor's emotional reactions to the work, and promotes ongoing assessment of counselor self-care as part of the supervision dialogue (Sommer & cox, 2005). When clinical supervision is separate from administrative supervision, it is found to be more helpful and effective (coady, Kent, & davis, 1990).…”
Section: Interpersonal Self: Relationshipsmentioning
confidence: 99%